2020
DOI: 10.3758/s13421-020-01070-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of tonal information during spoken-word recognition in Chinese: Evidence from a printed-word eye-tracking study

Abstract: Two experiments were conducted to investigate the extent to which the lexical tone can affect spoken-word recognition in Chinese using a printed-word paradigm. Participants were presented with a visual display of four words-namely, a target word (e.g., 象限, xiang4xian4, "quadrant"), a tone-consistent phonological competitor (e.g., 相册, xiang4ce4, "photo album"), or a tone-inconsistent phonological competitor (e.g., 香菜, xiang1cai4, "coriander"), and two unrelated distractors. Simultaneously, they were asked to li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 36 publications
3
25
1
Order By: Relevance
“…Finnish readers do encode (and use) vowel harmony information at a later processing stage, as we obtained clear evidence of an effect of vowel harmony when participants had to decide whether a letter string was a Finnish word or not (e.g., HÖPEÄ [harmonious pseudoword] produced longer "no" responses than HOPEÄ [disharmonious pseudoword]). Future research should examine the role of morpho-phonological features such as vowel harmony during word processing in sensory modalities that rely on serial input, such as reading VOWEL HARMONY AND WORD RECOGNITION 9 Finnish compound words in braille (see Fischer-Baum & Englebretson, 2016, for morphological effects in braille) or during spoken word recognition (e.g., using variants of the gating or visual world paradigms; e.g., Shen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Finnish readers do encode (and use) vowel harmony information at a later processing stage, as we obtained clear evidence of an effect of vowel harmony when participants had to decide whether a letter string was a Finnish word or not (e.g., HÖPEÄ [harmonious pseudoword] produced longer "no" responses than HOPEÄ [disharmonious pseudoword]). Future research should examine the role of morpho-phonological features such as vowel harmony during word processing in sensory modalities that rely on serial input, such as reading VOWEL HARMONY AND WORD RECOGNITION 9 Finnish compound words in braille (see Fischer-Baum & Englebretson, 2016, for morphological effects in braille) or during spoken word recognition (e.g., using variants of the gating or visual world paradigms; e.g., Shen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…First, the lexical tone of the phonological competitors was not manipulated in the current study. One of our prior studies showed that lexical tone affects the degree of activation of cohort competitors ( Shen et al, 2020 ), and thus it remains unclear how the lexical tone of rhymes might modulate the activation degree of rhyme competitors. This should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that phonological processing of words can be affected by the sentence predictability. For example, the lexical tone exhibits stronger constraining role during Chinese spoken word recognition in the predictive context compared to the neutral context or isolated word recognition; and a similar modulating role of lexical tone was found between the neutral context or isolated word recognition (Liu and Samuel, 2007;Shen et al, 2020). The mechanism underlying the prediction is assumed to be the pre-activation, that is, the activation occurs earlier before the presentation (Otten et al, 2007;Laszlo and Federmeier, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Compared with English words, 72% of modern Mandarin Chinese words are formed by two syllables, 24.87% are multisyllabic words (11.53% are three-syllable, 10.45% are four-syllable, 2.89% are five-syllable words), and only 5.68% are monosyllabic words (Lexicon of Common Words in Contemporary Chinese Research Team, 2008). To date, most experimental studies investigating the phonological processing of word recognition (e.g., syllabic or tonal information) in non-Indo-European languages have predominantly relied on monosyllabic words (e.g., Lee, 2007; Li et al, 2013, 2019; Malins & Joanisse, 2010; Sereno & Lee, 2015; Shen et al, 2021; Yang & Chen, 2022 for Chinese), and relatively few exceptions used disyllabic words (e.g., Huang et al, 2016; Shen at al., 2018; Teruya & Kapatsinski, 2019; for Japanese; Tzeng et al, 2006; Wang et al, 2021; for Chinese). Given that Malins and Joanisse (2010) concluded that native Chinese listeners showed different levels of phonological competition among words sharing word-initial information versus words sharing word-final information in Chinese spoken word recognition, they only manipulated monosyllabic words instead of disyllabic words.…”
Section: The Subsyllable and Syllable As Phonological Units In Englis...mentioning
confidence: 99%
“…The current evidence concerning this issue is mixed (Shen et al, 2021). Several studies have demonstrated that tones played a comparable and strong role in constraining Chinese spoken word recognition compared with the syllables (e.g., Lee, 2007; Liu & Samuel, 2007; Malins et al, 2014; Malins & Joanisse, 2010, 2012; Schirmer et al, 2005; Shen et al, 2021; Zhao et al, 2011). However, the proposal of the strong role of lexical tones has been also challenged by some studies on Chinese spoken word recognition (e.g., Hu et al, 2012; Sereno & Lee, 2015; Taft & Chen, 1992; Tong et al, 2008; Wiener & Turnbull, 2016; Ye & Connine, 1999; Zou et al, 2022).…”
mentioning
confidence: 99%